Służby ratunkowe w Tatrach = Emergency services in the High Tatras - Joanna Siminska; Sara Przybylska; Anna Świątkowska; Iwona Domarecka; Waldemar Miszewski; Krystyna Nowacka; Wojciech Hagner (Journal of Education, Health and Sport, 2017)
Siminska Joanna, Przybylska Sara, Świątkowska Anna, Domarecka Iwona, Miszewski Waldemar, Nowacka Krystyna, Hagner Wojciech. Służby ratunkowe w Tatrach = Emergency services in the High Tatras. Journal of Education, Health and Sport. 2016;6(11):404-411. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.168477